A correlative study of uric acid with lipid profile - Sarmah, Devajit; Sharma, Booloo (Asian Journal of Medical Sciences, 2013)
Objective: the study was conducted to verify the association of hyperuricemia with lipid profile in a group of Assamese people so as to take necessary precautions from developing future cardiovascular disease (CVD). Methods: lipid profile (total cholesterol, triglycerides, HDL and LDL) were estimated in sixty hyperuricemic Assamese people who had no previous history of CVD to ascertain the pattern of their association between uric acid and lipid profile if any. Results: The study proves a significant positive correlation (p < 0.005) between uric acid and TC, TG and LDL, and a significant negative correlation (p < 0.005) between uric acid and HDL. Conclusion: The study thus shows that hyperuricemia is associated with dyslipidemia which may predispose to future CVD. So treating such subject for hyperuricemia and dyslipidemia can very well reduce cardiovascular morbidity. DOI: http://dx.doi.org/10.3126/ajms.v4i2.7893 Asian Journal of Medical Sciences 4(2013) 8-14